Revisão sistemática da gamificação no Ensino de Física na sala de aula do estado de São Paulo - Silva, Rodolpho Adão Dias da (Universidade Federal de São Carlos, 2025)
This study aims to conduct a systematic review of published materials on the use of gamification in physics teaching as an active learning methodology. Six studies were selected using descriptors defined in the Web of Science database for this review. This review presents a brief description of the concept of gamification, as well as an analysis of aspects such as the influence of this methodology on teacher-student communication and the feasibility of the adopted gamification strategies, considering the context of the state of São Paulo.
Systematic review of gamification in Physics Teaching in the classroom of the state of São Paulo
Keywords: Revisão sistemática; Gamificação; Ensino médio; Systematic review; Gamification; High school; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL; 4. Educação de Qualidade